SenSORCER: A Framework for Managing Sensor-Federated Networks - Bhosale, S.; Sobolewski, M. (2009 International Conference on Parallel Processing Workshops, 2009)
Despite many technology advances, the limited computing power of sensors encumber them from taking part in service-oriented architectures. In recent years, the sensor-networking subject has been extensively studied, with the focus on efficient usage of energy in sensors and efficient usage of sensor node processing power. However, providing sensor nodes with the relevant computing power and network sensor management is seldom addressed. With the availability of federated meta-computing environments, sensors can participate in service oriented computing, by exporting sensor probe data with relevant processing as a network service. The framework introduced in this paper allows for building highly scalable and dynamic sensor networks, providing sensors with corresponding federated computing environment. A novel approach using the SORCER metacomputing model to integrate several different sensors and sensor networks into a dynamic service-oriented sensor network is presented. The framework makes use of provisioning mechanism, which autonomically allocates required resources to sensor services. Furthermore, the dynamically typed language, Groovy, provides the runtime computing mechanism involving variables of sensor services. The framework is generic and extensible and allows incorporating different standard and non-standard sensor technologies. It also helps expedite the development process for service-to-service applications involving sensor data.